Profil Kemampuan Aerobic Endurance, Maximum Strength, Power dan Strength Endurance Atlet MMA Klub Iron Sheep Kabupaten Garut - Mochamad Hoky Aldiansyah Hoky Mochamad; Alen Rismayadi; Dadan Mulyana (Fakultas Pendidikan Olahraga dan Kesehatan, Universitas Pendidikan Indonesia, 2022)
This study aims to determine the profile of aerobic endurance, maximum strength, power and endurance of MMA athletes at the Iron Sheep Club, Garut Regency. The components measured were components of physical condition, namely aerobic endurance, maximum strength, explosive power and strength endurance. This type of research is descriptive research. The method used is a survey, with data collection techniques using tests and measurements. The research design uses a simple paradigm using the One-shot method approach. The population in this study were all athletes, totaling 10 people using a total sampling technique. The instruments used are; (1) aerobic endurance was measured using a bleep test in minutes, (2) maximum strength was measured using a bench press test in kilograms, (3) strength was measured using push ups in seconds, (4) strength endurance was measured by pulling ups in units of seconds. Data analysis used descriptive percentage. The results showed that the profile of the physical condition of the MMA athletes at the Iron Sheep Club of Garut Regency was in the very low 10%, low 30%, moderate 40%, high 10% and very high 10% categories.